Critical success factors for ERP implementation in a Fortis hospital: an empirical investigation. Issue 4 (8th July 2014) - Garg, Poonam; Agarwal, Divya
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine the success of enterprise resource planning (ERP) implementation based on five identified items, i.e. top management commitment (TMC), user involvement (UI), business process reengineering (BPR), project management (PM) and ERP teamwork and composition (TWC) factors at Fortis hospital, Bangalore, India. It also tests a number of hypotheses and examines the hypothetical relationships among critical success items and success of ERP implementation. Design/methodology/approach – Empirical data were collected via a survey questionnaire/interview technique. A structured interview was planned and conducted with key executives of Fortis hospital who were familiar with success of ERP implementation progress as well as examination of company documentation supported by literature. Findings – A significant relationship was found between TMC, UI, BPR, PM and ERP TWC with success of ERP implementation at Fortis hospital. Originality/value – The value of this paper is that it presents any hospital wishing to implement ERP with a set of critical success factors. Understanding the critical success factors would lead to a smoother implementation in hospital industry. Although as a single case study the ability to generalize the findings is narrow, support from literature and experiences add the knowledge to ERP implementation in healthcare sector in India.